Pedagogical and inclusive clothing as a child learning resource - Bononi, Juliana (2022)
The present work, of literature review, has as main objective to seek connections between school inclusion, didactic learning resources and children's clothing, verifying if the latter can be used in the development of relationships, perceptions and deductions that children make during interaction with objects, through creative and meaningful learning. It can be said that clothing is a pedagogical and playful object, and its elements can be used as a learning resource as they help children in the development of perception and interpretation through sensory exploration and social interaction. Since dressing is like a personal construction, it helps in the formation of self-image and offers the child user another point of view about himself, making him feel more confident, beautiful and even a “superhero”. However, it is necessary to train teachers and teachers so that these professionals are able to help children in this process.